The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.14309/ctg.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and the Susceptibility of COVID-19 and the Risk of Severe COVID-19: A Mendelian Randomization Study

Abstract: INTRODUCTION:Previous observational studies have found that the susceptibility of coronavirus disease 2019 (COVID-19) and the risk of severe COVID-19 are not increased in patients with celiac disease (CeD). However, the findings of observational studies are prone to bias due to reverse causation and confounding factors, especially in the case of a newly emerged disease. In this study, we aimed to further clarify the underlying relationship by both observational and Mendelian randomization (MR) analysis.METHODS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…930 articles were further excluded after considering the title and abstract, generating 68 papers for satisfactory article review for plausible consideration in this analysis. Eventually, 11 articles consisting of 44,378 celiac patients were incorporated into this meta‐analysis based on exhaustive evaluation and inclusion criteria 8,14–23 . The baseline characteristics of the incorporated studies are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…930 articles were further excluded after considering the title and abstract, generating 68 papers for satisfactory article review for plausible consideration in this analysis. Eventually, 11 articles consisting of 44,378 celiac patients were incorporated into this meta‐analysis based on exhaustive evaluation and inclusion criteria 8,14–23 . The baseline characteristics of the incorporated studies are summarised in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, 11 articles consisting of 44,378 celiac patients were incorporated into this meta-analysis based on exhaustive evaluation and inclusion criteria. 8,[14][15][16][17][18][19][20][21][22][23] The baseline characteristics of the incorporated studies are summarised in Table 1. Four of these included studies were from Italy, followed by the USA with two reports and one from Iran, Sweden, and the United Kingdom.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Lastly, observational studies examined the risk of severe COVID-19 and mortality in patients with celiac disease. These studies were not specific to pediatrics, but overall, they did not find an increased risk of severe COVID-19 in individuals with celiac disease and compliant with a gluten-free diet [27 ▪ ,29].…”
Section: Covid-19 and Celiac Diseasementioning
confidence: 92%
“…During the COVID-19 pandemic, studies explored SARS-CoV-2 as a potential trigger for different autoimmune conditions. Although type 1 diabetes became more frequently diagnosed [25 ▪ ], studies failed to demonstrate an increased incidence of celiac disease during the pandemic [26,27 ▪ ]. It is unclear if this was the result of the increased hygienic measures leading to decreased exposure to SARS-COV-2 and other viruses typically associated with an increased risk of developing celiac disease such as enteroviruses, adenoviruses, and rotaviruses.…”
Section: Covid-19 and Celiac Diseasementioning
confidence: 99%
“…83 Also adult studies have unequivocally shown a similar incidence of COVID-19 in CeD as in the general journals.sagepub.com/home/tag TherapeuTic advances in Gastroenterology population. [84][85][86] Likewise, a large US study (TriNETX) found no significantly increased risk of hospital admission, critical care, or death from COVID-19. 87…”
Section: Celiac Disease and Risk Of Covid-19mentioning
confidence: 99%